The Effectiveness of Antenatal Care with a Gender Responsive Approach - Erika Yulita Ichwan; Yeniar Susana; Gita Nirmala Sari (Universitas Andalas, 2022)
Maternal Mortality Rate (MMR) is one of the indicators in determining the degree of health of a nation. One of the causes of maternal death is related to the problem of gender inequality in society. The role of midwives in providing gender-responsive services is needed to realize welfare and health for all. This study aims to determine the effectiveness of the gender approach in antenatal care at the Midwife Independent Practice Center. This research uses a descriptive qualitative method with in-depth interviews and data analysis using triangulation of sources, techniques and experts. Primary data were obtained using interview guideline sheets from 6 informants, which included 2 midwives and 2 pregnant women who did not understand antenatal care with gender responsiveness and their partners. The results of the study on the effectiveness of the gender approach in antenatal care at the Midwife E Independent Practice Place is assessed from indicators of target accuracy, socialization, achievement of goals and monitoring, it can be said to be quite effective because the implementation already involves the participation of pregnant women and their partners. However, there needs to be a guideline that regulates gender-responsive care. Suggestion: Establish a specific guideline governing gender-responsive midwifery care standards by both professional organizations and related agencies.